2000
DOI: 10.1590/s0100-879x2000001000006
|View full text |Cite
|
Sign up to set email alerts
|

Salivary cortisol as a tool for physiological studies and diagnostic strategies

Abstract: Salivary cortisol is an index of plasma free cortisol and is obtained by a noninvasive procedure. We have been using salivary cortisol as a tool for physiological and diagnostic studies, among them the emergence of circadian rhythm in preterm and term infants. The salivary cortisol circadian rhythm in term and premature infants was established between 8 and 12 postnatal weeks. In the preterm infants the emergence of circadian rhythm was parallel to the onset of sleep rhythm. We also studied the use of salivary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
12

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 29 publications
1
37
0
12
Order By: Relevance
“…As the AUCg analysis showed, the general cortisol output was not affected by the HF-rTMS experiment, indicating that in line with animal studies stress-responses did not interfere with our data (Hedges et al, 2002). Furthermore, to reduce possible stressrelated responses, we used of salivettes as this has certain advantages over blood samples: sampling is noninvasive, it can frequently be repeated, and it avoids stress induction (painless) (Castro et al, 2000).…”
Section: Discussionsupporting
confidence: 66%
“…As the AUCg analysis showed, the general cortisol output was not affected by the HF-rTMS experiment, indicating that in line with animal studies stress-responses did not interfere with our data (Hedges et al, 2002). Furthermore, to reduce possible stressrelated responses, we used of salivettes as this has certain advantages over blood samples: sampling is noninvasive, it can frequently be repeated, and it avoids stress induction (painless) (Castro et al, 2000).…”
Section: Discussionsupporting
confidence: 66%
“…The correlation between free serum cortisol and salivary cortisol levels varies from patients with excess cortisol concentration, such as Cushing disease and psychiatric patients. 15 Most studies available on salivary cortisol are in healthy volunteers or noncritically ill subjects with excess production of cortisol, and in these patients the correlation between salivary cortisol and free serum cortisol levels is 80% to 90%. 19 Sample size was calculated using single correlations.…”
Section: Discussionmentioning
confidence: 99%
“…12 Studies in healthy volunteers and for the evaluation of patients with hypothalamus-pituitary-adrenal axis disease have showed an excellent correlation between free or unbound serum and salivary cortisol levels, although the relationship is nonlinear and correlation is more closely related at lower levels (when total serum concentration is , 16.3 m g/dL). [13][14][15] We evaluated the correlation between salivary cortisol and total serum cortisol with free serum cortisol levels in adult medical intensive care patients with septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…6 A negative correlation of morning salivary cortisol concentrations and total cortisol concentration with body mass index was found in children with recurrent abdominal pain of psychosomatic origin in another study. 2 These authors also found in their cohort of 159 healthy girls and 147 boys that salivary cortisol concentration was dependent on the time of sampling, age and menarche.…”
mentioning
confidence: 88%